ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 16/PUU-XVI/2018 TENTANG PEMBATALAN PERLUASAN KEWENANGAN MAHKAMAH KEHORMATAN DEWAN - Yohanes Nafta Irawan; Retno Saraswati; Esmi Warassih Pujirahayu (Faculty of Law, Universitas Diponegoro, 2019)
This research analyzes the Constitutional Court Decision Number 16/PUU-XVI/2018 that has been canceled Article 122 letter l and Article 245 section (1) from the Law Number 2 of 2018. Article 122 letter l is related to legal steps or other steps that can be taken by The Council Honor Court in the event that there is individuals, groups of people, or legal entities who criticize the House of Representatives or members of the House of Representatives, while Article 245 section (1) relates to the consideration given by the Council Honor Court in the event of a summons or request for investigation into members of the House of Representatives. Both articles are considered unconstitutional and contain an extension of the authority of the Council Honor Court. The appearance of the two articles was influenced by the political configuration of the authoritarian House of Representatives and the naming of the Council Honor Court which deemed inappropriate.